Transient Perivascular Inflammation of the Carotid Artery as a Poorly Recognized Cause of Neck Pain - Greutert, Sophie; Schlomer, Tatiana; Righini, Marc (TH Open, 2024)
Transient perivascular inflammation of the carotid artery (TIPIC) syndrome, historically named idiopathic carotidynia or Fay syndrome, is a rare condition characterized by inflammation and pain in the carotid artery. The diagnosis requires a specific clinical–radiological presentation. We describe a 37-year-old female who presented with headaches and left neck pain and was diagnosed with TIPIC syndrome with temporary perivascular infiltration.
Keywords: TIPIC syndrome; temporary perivascular infiltration; carotidynia; Fay syndrome; neck pain